Trumponomics – Mercantilism of the 21st Century? - Večeř, Marek; Janíčko, Martin, 1983-; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
This diploma thesis deals with Trumponomics, a specific concept of the economic policy of the new US administration, which is aimed at reducing the long-term US current account deficits. The theoretical part first introduces the theoretical framework of Trumponomics, and then deals with alternative views of economists on causes and solutions to the problem of long-term US current account deficit. In the empirical part, VAR models for four different periods of the US current account deficits development are designed, to capture the key factors that contributed to the US current account deficits in each of the examined period. The results suggest that the rise in the US trade deficit was due to both the changes in the fundamentals of the US economy and partly to the protectionist practices of US trading partners.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses